Theoretical Sufism and Sharia regulations - Halilović Seid (Kom: Časopis za Religijske Nauke)
Sharia means formal regulations on legal and ethical issues, that is, God's commandments and prohibitions that a Muslim should follow in the everyday contexts of his physical life. If someone does not thoroughly implement the Sharia regulations, such as the regulations on prayer or fasting, he will not be able to properly approach the sphere of spirituality and it will even be meaningless to talk about the results of his spiritual and mystical development. Therefore, he will not have credible intuitive power and the most refined ontological and metaphysical secrets of the universe, which are discussed in theoretical Sufism, will not be revealed to him. The most prominent representatives of theoretical Sufism assure us that Islamic jurisprudence and ethics are a necessary introduction to valid mystical experiences and that it is necessary to adhere to all Sharia regulations because they are a condition for success both at the beginning and in all later stages of the mystical journey. They warn that the slightest neglect of the importance of God's precepts in the form of Sharia will be the cause of the mystic's spiritual downfall. By analyzing the content of the reference works of the members of Ibn ʻArabī's school of theoretical Sufism, we will see that Sharia plays the role of the guardian of the mystic's intuitive experiences. The guardian will not allow the spiritual traveler in the protected area to be endangered and will protect his pure mystical knowledge from being discredited and distorted. We will also realize that all formal Sharia regulations actually hide deep spiritual secrets. If we approach the analysis of Sharia regulations in their esoteric layers with a grounded mystical methodology, we will understand that the original mystical teachings of Islam are hidden in the Sharia itself and at the heart of the Sharia rituals in which the Muslim affirms his ontological need to repentantly obey and serve the absolute being of God.